2020
DOI: 10.1001/jamanetworkopen.2020.23644
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Vitamin C for Iron Supplementation in Adult Patients With Iron Deficiency Anemia

Abstract: Key Points Question Are the effects of oral iron supplements alone equivalent to a regimen of oral iron supplements plus vitamin C in the treatment of iron deficiency anemia? Findings In this randomized clinical trial that included 440 adults with iron deficiency anemia, the mean change in hemoglobin level after 2 weeks was 2.00 g/dL in the oral iron supplements plus vitamin C group, compared with 1.84 g/dL in the oral iron supplements–only group. This diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 9 publications
2
62
1
9
Order By: Relevance
“…125 Despite previous suggestions of benefit, 121 coadministration of vitamin C with oral IRT is not recommended-a recent large randomised controlled trial has confirmed that it neither enhances the haematological response or rate of iron loading, nor diminishes side effects. 126 Iron absorption from oral preparations is determined by a complex interplay involving total body iron stores, erythropoietic activity of the bone marrow, recent exposure of the small intestine to iron and systemic inflammation. 35 127-131 Hepcidin is the most important inhibitor of iron absorption.…”
Section: Oral Irtmentioning
confidence: 99%
“…125 Despite previous suggestions of benefit, 121 coadministration of vitamin C with oral IRT is not recommended-a recent large randomised controlled trial has confirmed that it neither enhances the haematological response or rate of iron loading, nor diminishes side effects. 126 Iron absorption from oral preparations is determined by a complex interplay involving total body iron stores, erythropoietic activity of the bone marrow, recent exposure of the small intestine to iron and systemic inflammation. 35 127-131 Hepcidin is the most important inhibitor of iron absorption.…”
Section: Oral Irtmentioning
confidence: 99%
“…Vitamin C interacts with iron to enhance adequate absorption of iron from diets. The interaction gives rise to the formation of an iron chelate complex at acid pH, which enhances iron solubility in the small intestine, thereby increasing its utilization in the duodenum ( Lynch & Cook, 1980 ; Beck, 2014 ; Li et al, 2020 ). On the other hand, the synergistic action of vitamins and minerals in the protection of organism at the cellular level has been recorded for vitamin E, C, carotenoid and selenium, as well as other important trace elements as an antioxidant component in diets.…”
Section: Discussion Of Literature Synthesismentioning
confidence: 99%
“…Among others, ascorbic acid or vitamin C is the most effective enhancer of non-heme iron absorption, thus should be provided along within the meals rich in iron content. 11 If necessary, additional portion of iron and vitamin C fortified food can help increase the hemoglobin level, 12 before last decision for provision of iron 13 and/or micronutrient supplement is given to those workers with low hemoglobin status.…”
Section: Discussionmentioning
confidence: 99%